La diáspora akán: los cuentos de Anancy en Limón y el Caribe colombiano insular - Pochet Rodríguez, Lina (2012)
This article deals with a review about the akan diasporization in Jamaica, the Colombian archipelago of San Andrew, Old Providence and Saint Catherine, and the Costa Rican Province of Limon. The point of departure is the akan ethnic groups known as the akan, whose territory is located in Ghana, Ivory Coast and Togo. Then, text is related to the arrival of the akan to the Caribbean, specifically to Jamaica, as a result of the world powers participation in the slave trade on the West Africa’s coasts. Finally, the article approaches the diasporization of the Anancy Stories to the Colombian and Costa Rican territories.